(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
This article endeavors to break down why Rani Gaidinliu, who was an opportunity warrior and social and religious reformer, was quick to save the identity and culture of her cognate tribe1—the Zeme, Liangmai, RongmaiKabui and Npui. Does Heraka—a socio-religious development begun by Haipou Jadonang and later created by the Rani—turn into an instrument of ’social revivalism’ and go about as a way to join cognate tribes? For what reason do we compare Heraka with the Hindutva ideologues, for example, the Vishwa Hindu Parishad (VHP) and Rashtriya Swayamsevak Sangh (RSS) that position Rani Gaidinliu in another soul of patriotism and identity as the solitary lady profound and political hero of Northeast India? She utilized Heraka with governmental issues to satisfy her objectives in battling the British. Utilizing the meeting technique, I addressed chosen respondents, especially older folks and community pioneers, about Rani Gaidinliu. Her story delineates a soundness that could support underestimated and imperceptible ladies to end up sociopolitical and otherworldly pioneers, interrogating male centric society and bringing concerning strengthening and social incorporation.